Local structure and defects in ion irradiated KTaO3. (12th March 2018) - Zhang, F X; Xi, J; Zhang, Y; Tong, Yang; Xue, H; Huang, R; Trautmann, C; Weber, W J
Abstract: The modification of the local structure in cubic perovskite KTaO3 irradiated with 3 MeV and 1.1 GeV Au ions is studied by Raman and x-ray absorption spectroscopy, complemented by density functional theory (DFT) calculations. In the case of irradiation with 3 MeV Au ions where displacement cascade processes are dominant, the Ta L3 -edge x-ray absorption measurements suggest that a peak corresponding to the Ta–O bonds in the TaO6 octahedra splits, which is attributed to the formation of TaK antisite defects that are coupled with oxygen vacancies, V O . This finding is consistent with the DFT calculations. Under irradiation with 1.1 GeV ions, the intense ionization and electronic energy deposition lead to a blue shift and an intensity reduction of active Raman bands. In the case of sequential irradiations, extended x-ray absorption fine structure measurements reveal a decrease in concentration of coupled TaK - V O defects under subsequent irradiation with 1.1 GeV Au ions.